(3fHP ef eWGQMGJ TYQGA GdYUQs
(3BNQgG (B:s
(3JfJgi HChd ebWYGJ aNQ GdOjf Hf ecGfS s
(3Hg VHWs
(3efge Gdehdi HOQ GdOjf GdOeGejfi hTgGH GdOjf Hf MLQ hGdehdi aNQ GdOjf Hf ecGfSs
(3hRjf GdOjf Hf GdYLei hcdge fHZhG ai GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B21 - (3U (B539 s
Keywords: (3GdCOHs